Factors Influencing Consumer Decisions In Purchasing Mobile Phones At SMS Shop Purwodadi 1 - Myra Heltyani; Athoillah (LPPM Universitas An Nuur, 2021)
Background: The development of increasingly advanced technology, especially smartphones. Smartphones are also a means of long-distance communication and to obtain the latest information. The problem with the SMS Shop Purwodadi Branch 1, the promotion only relies on Facebook social media and through Whatsapp Group. To increase SMS Shop salesPurpose: This study aims to determine the factors that influence consumer purchasing decisions that are influenced by promotion and price variables.Methods: This study associative research. The population in this study was the entire community of Purwodadi with a sample of 100 with certain criteria.Conclusion: From the results of the study it can be concluded that promotion has a strong influence on consumer decisions to purchase mobile phone products. However, price has no influence on consumer purchasing decisions. This theory can be put into practice in the SMS Shop business to carry out wider promotions and make competitive prices.Suggestion: In the future, we plan to adding other variables that can increase smartphone sales.